Diffusion Tensor Imaging of Skeletal Muscle Contraction Using Oscillating Gradient Spin Echo - Mazzoli, Valentina; Moulin, Kevin; Kogan, Feliks; Hargreaves, Brian A.; Gold, Garry E. (Frontiers in Neurology, 2021)
Diffusion Tensor Imaging (DTI) measures water diffusion in skeletal muscle tissue, and allows for muscle assessment in abroad range of neuromuscular diseases. However, current DTI measurements, typically performed using Pulsed Gradient Spin Echo (PGSE) diffusion encoding, are limited to the assessment of non-contracted musculature, therefore providing limited insight into muscle contraction mechanisms and contraction abnormalities. In this study we propose the use of an Oscillating Gradient Spin Echo (OGSE) diffusion encoding strategy for DTI measurements to mitigate the effect of signal voids in contracted muscle and obtain reliable diffusivity values. Two OGSE sequences with encoding frequencies of 25 Hz and 50 Hz were tested in the lower leg of 5 healthy volunteers with relaxed musculature and during active dorsiflexion and plantarflexion, and compared to a conventional PGSE approach. A significant reduction of areas of signal voids using OGSE compared to PGSE was observed in the Tibialis Anterior for the scans obtained in active dorsiflexion and in the Soleus during active plantarflexion. The use of PGSE sequences led to unrealistically elevated Axial Diffusivity values in the Tibialis Anterior during dorsiflexion and in the Soleus during plantarflexion, while the corresponding values obtained using the OGSE sequences were significantly reduced. Similar findings were seen for Radial Diffusivity, with significantly higher diffusivity measured in plantarflexion in the Soleus muscle using the PGSE sequence. Our preliminary results indicate that DTI with OGSE diffusion encoding is feasible in human musculature and allows to quantitatively assess diffusion properties in actively contracting skeletal muscle. OGSE holds great potential to assess microstructural changes occurring in skeletal muscle during contraction, and for non-invasive assessment of contraction abnormalities in patients with muscle diseases.